ANALISIS KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL PERBANDINGAN - Regina Nabila Basuki; Siti Chotimah (IKIP Siliwangi, 2021)
This research intends to examine the student's misconception in completing comparative story problems. This research uses descriptive qualitative research methods, and the results will be analyzed to define the student’s level of capability on comparison materials. The research provides a test instrument with five problems of comparative story problems created based on bloom’s cognitive domain, with details 1 of the cognitive domain C2, C3, C5, and 2 questions of C6. The subjects in this research were 23 students of class 8 at one of the state junior high schools in Cimahi. Data analysis in this research is data reduction, data display, and verification. The results indicate that there was 1 student with high capability, 1 student with medium capability and, 21 students with low capability, the mistake made, including conceptual errors, principle errors, and algorithm errors, while the average class acquiring was 36.11%. Based on this, the conclusion is the student's capability to solve comparative material problems is still low so that increased capability is required.